2017
DOI: 10.1136/jim-2017-000443
|View full text |Cite
|
Sign up to set email alerts
|

The Risk of Ischemic Events Increased in Patients with Asymptomatic Carotid Stenosis with Decreased Cerebrovascular Reserve

Abstract: Identifying high-risk patients with asymptomatic carotid stenosis (ACS) is necessary regardless of whether intensive medical therapy or aggressive treatment is applied. In order to assess the relationship between cerebrovascular reserve (CVR) measured by perfusion CT with inhalation of CO and the risk of ischemic events in ACS, this long-term follow-up study was conducted. Forty-five patients with ACS who underwent the examination of CVR measured by perfusion CT with inhalation of CO were collected and followe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…CT perfusion (CTP) is a well-studied and straightforward method for assessing cerebrovascular reserve. Studies have shown that asymptomatic patients with carotid artery stenosis who have abnormal cerebrovascular reserve on CTP are more likely to develop ipsilateral ischemic events (32). In addition, studies have found that hemodynamic changes on CTP can be reversed with carotid artery stenting in both symptomatic and asymptomatic patients (Figure 1) (33)(34)(35).…”
Section: Markers Of Hemodynamic and Perfusional Abnormalitiesmentioning
confidence: 99%
“…CT perfusion (CTP) is a well-studied and straightforward method for assessing cerebrovascular reserve. Studies have shown that asymptomatic patients with carotid artery stenosis who have abnormal cerebrovascular reserve on CTP are more likely to develop ipsilateral ischemic events (32). In addition, studies have found that hemodynamic changes on CTP can be reversed with carotid artery stenting in both symptomatic and asymptomatic patients (Figure 1) (33)(34)(35).…”
Section: Markers Of Hemodynamic and Perfusional Abnormalitiesmentioning
confidence: 99%
“…Webster et al and Yonas et al also showed in Xe-CT studies an association between a decreased CVR and risk of stroke in patients with severe carotid stenosis (38,39). These results were corroborated by two other studies using CT perfusion and doppler ultrasound (40,41). A meta-analysis has identified an increased OEF as an independent predictor of stroke in carotid stenosis or occlusion (42).…”
Section: Hemodynamic and Cerebrovascular Reactivity (Cvr) Studiesmentioning
confidence: 78%
“…In the subgroup of studies focusing on participants with severe stenosis only (9 cohorts with 2128 participants; mean follow-up period, 2.8 years; range, 1.4-6.5 years), the incidence of ipsilateral ischemic cerebrovascular events was 3.7 events per 100 person-years (95% CI, 1.9-6.0 events per 100 person-years). The incidence of ipsilateral ischemic cerebrovascular events was also higher in patients with high-risk features (7.3 events per 100 person-years; 95% CI, 2.0-15.0 events per 100 person-years) (Figure 1) than in those without high-risk features (1.7 events per 100 person-years; 95% CI, 0.6-3.3 events per 100 person-years) (eFigure 18 in the Supplement), with an OR of 3.2 (95% CI, 1.7-5.9; I 2 = 39.6%) (Table 3).…”
Section: Resultsmentioning
confidence: 98%
“…The incidence of ipsilateral ischemic events was higher in patients with high-risk features (4.3 events per 100 person-years; 95% CI, 2.5-6.5 events per 100 person-years) (Figure 1; eFigure 17 in the Supplement) than in those without high-risk features (1.2 events per 100 person-years; 95% CI, 0.6-1.8 events per 100 person-years) (eFigure 18 in the Supplement), with a corresponding OR of 3.0 (95% CI, 2.1-4.3; I 2 = 48.8%) (Figure 2). This association between the presence of high-risk plaque and the risk of ipsilateral ischemic cerebrovascular events was also observed in pooling data from the 7 studies that reported adjusted HRs (pooled HR, 3.0; 95% CI, 1.8-4.2; I 2 = 0%) (eFigure 2 in the Supplement).…”
Section: Resultsmentioning
confidence: 99%